Do Tax Audits Strengthen or Weaken the Effect of Tax Knowledge on Tax Compliance? (Evidence from MSMEs in Karanganyar, Indonesia) - Helti Nur Aisyiah; Bambang Sutopo (Academic Bright Collaboration, 2026)
Purpose – This study aims to examine the effect of tax knowledge on MSME tax compliance and to investigate the moderating role of tax audits in this relationship, particularly whether tax audits strengthen or weaken the influence of tax knowledge on tax compliance. Methods – This research employs a quantitative approach using primary data collected from 98 individual MSME taxpayers registered at the Karanganyar Primary Tax Office (KPP Pratama Karanganyar), Indonesia. Data were gathered through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis integrates the Theory of Planned Behavior (TPB) and deterrence theory to explain how internal knowledge and external enforcement mechanisms influence tax compliance behavior. Findings - The results show that tax knowledge has a positive and significant effect on tax compliance (β = 0.488, p < 0.001). Tax audits also have a positive and significant direct effect on tax compliance (β = 0.214, p = 0.008). However, the interaction between tax knowledge and tax audits reveals a significant negative moderating effect (β = −0.233, p = 0.030), indicating that stronger audit enforcement weakens the positive influence of tax knowledge on tax compliance. The model explains 49.7% of the variance in tax compliance (R² = 0.497). The findings indicate that tax audits weaken rather than strengthen the effect of tax knowledge on MSME tax compliance, suggesting the presence of a crowding-out effect in which excessive enforcement may reduce taxpayers’ intrinsic motivation to comply. Research Implication - The findings suggest that improving taxpayer compliance requires a balanced strategy combining tax education with proportional audit enforcement. Originality - This study contributes to the tax compliance literature by integrating TPB and deterrence theory and providing empirical evidence of the negative moderating role of tax audits in MSME tax compliance in Indonesia.